The Students' Learning Difficulties at the Open University Webinar Tutorial - Gede Suwardika; Agus Tatang Sopandi; Putu Oktap Indrawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The Open University (UT) is one of the pioneer universities that implement distance learning. However, students still encounter learning difficulties which become obstacles in distance learning. The purpose of this research is to analyses the construct of learning difficulties of students’ learning at Open University and to compare the contribution of indicator variables to the construct. This research uses a combination method of Concurrent Embed model, the primary method used is factor analysis method (EFA and CFA) and qualitative descriptive method as a secondary method. The research respondents were 126 students who had attended the webinar tutorial (Tuweb) at least twice and voluntarily filled out the questionnaire. Primary data were collected through online questionnaires and interviews. Quantitative data were analyzed using EFA and CFA, while quantitative data were analyzed descriptively qualitatively. The results showed that there are six factors of learning difficulties, each of which consisted of 4-9 indicator variables. The indicator variables that contribute the most to learning difficulties in Tuweb according to student perceptions include: (1) there are no clear guidelines regarding the online learning procedures that are carried out; (2) learning materials/content delivered by online tutors are difficult to understand; (3) the internet signal is not stable/good from students’ location; (4) students' families are constrained in providing facilities for online learning/webinar tutorials due to low income; (5) students do not understand how to study online; (6) The device used by the tutor is constrained during the Tuweb learning process.